Clinical Outcomes, Costs, and Cost-effectiveness of Strategies for People Experiencing Sheltered Homelessness During the COVID-19 Pandemic - Travis P. Baggett; Justine A. Scott; Mylinh H. Le; Fatma M. Shebl; Christopher Panella; Elena Losina; Clare Flanagan; Jessie M. Gaeta; Anne Neilan; Emily P. Hyle; Amir Mohareb; Krishna P. Reddy; et al. (My University, 2020)
Importance: Approximately 356,000 people stay in homeless shelters nightly in the US. They are at high risk for COVID-19. Objective: To assess clinical outcomes, costs, and cost-effectiveness of strategies for COVID-19 management among sheltered homeless adults. Design: We developed a dynamic microsimulation model of COVID-19 in sheltered homeless adults in Boston, Massachusetts. We used cohort characteristics and costs from Boston Health Care for the Homeless Program. Disease progression, transmission, and outcomes data were from published literature and national databases. We examined surging, growing, and slowing epidemics (effective reproduction numbers [Re] 2.6, 1.3, and 0.9). Costs were from a health care sector perspective; time horizon was 4 months, from April to August 2020. Setting & Participants: Simulated cohort of 2,258 adults residing in homeless shelters in Boston. Interventions: We assessed daily symptom screening with polymerase chain reaction (PCR) testing of screen-positives, universal PCR testing every 2 weeks, hospital-based COVID-19 care, alternate care sites [ACSs] for mild/moderate COVID-19, and temporary housing, each compared to no intervention. Main Outcomes and Measures: Cumulative infections and hospital-days, costs to the health care sector (US dollars), and cost-effectiveness, as incremental cost per case prevented of COVID-19. Results: We simulated a population of 2,258 sheltered homeless adults with mean age of 42.6 years. Compared to no intervention, daily symptom screening with ACSs for pending tests or confirmed COVID-19 and mild/moderate disease led to 37% fewer infections and 46% lower costs (Re=2.6), 75% fewer infections and 72% lower costs (Re=1.3), and 51% fewer infections and 51% lower costs (Re=0.9). Adding PCR testing every 2 weeks further decreased infections; incremental cost per case prevented was $1,000 (Re=2.6), $27,000 (Re=1.3), and $71,000 (Re=0.9). Temporary housing with PCR every 2 weeks was most effective but substantially more costly than other options. Results were sensitive to cost and sensitivity of PCR and ACS efficacy in preventing transmission. Conclusions & Relevance: In this modeling study of simulated adults living in homeless shelters, daily symptom screening and ACSs were associated with fewer COVID-19 infections and decreased costs compared with no intervention. In a modeled surging epidemic, adding universal PCR testing every 2 weeks was associated with further decrease in COVID-19 infections at modest incremental cost and should be considered during future surges.
Keywords: Homelessness, COVID-19, cost-effectiveness analysis, simulation model